2020
DOI: 10.3390/ijerph17197175
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and Population-Based Evidence for COVID-19 Early Circulation in the East of France

Abstract: Background: Understanding SARS-CoV-2 dynamics and transmission is a serious issue. Its propagation needs to be modeled and controlled. The Alsace region in the East of France has been among the first French COVID-19 clusters in 2020. Methods: We confront evidence from three independent and retrospective sources: a population-based survey through internet, an analysis of the medical records from hospital emergency care services, and a review of medical biology laboratory data. We also check the role played in v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…By April 4, 2020, local community transmission was reported in all continents and over 1 million cases of COVID-19 had been confirmed worldwide. Although dedicated surveillance and contact tracing did not identify local transmission before the second half of February in Europe, there is accumulated evidence that SARS-CoV-2 circulated in early January 2020 in the East of France [2] and environmental studies suggest that the virus could have been present in December 2019 in Northern Italy [3]. A recent investigation of the presence of SARS-CoV-2 antibodies in 959 adults participating to a trial in Italy with blood samples collected between September 2019 to February 2020 identified 111 (11.6%) samples with a positive receptorbinding protein specific enzyme-linked immunosorbent assay (ELISA), among which 4 samples collected in October, 1 in November and 1 in February were also positive in a qualitative microneutralization assay [4].…”
Section: Introductionmentioning
confidence: 99%
“…By April 4, 2020, local community transmission was reported in all continents and over 1 million cases of COVID-19 had been confirmed worldwide. Although dedicated surveillance and contact tracing did not identify local transmission before the second half of February in Europe, there is accumulated evidence that SARS-CoV-2 circulated in early January 2020 in the East of France [2] and environmental studies suggest that the virus could have been present in December 2019 in Northern Italy [3]. A recent investigation of the presence of SARS-CoV-2 antibodies in 959 adults participating to a trial in Italy with blood samples collected between September 2019 to February 2020 identified 111 (11.6%) samples with a positive receptorbinding protein specific enzyme-linked immunosorbent assay (ELISA), among which 4 samples collected in October, 1 in November and 1 in February were also positive in a qualitative microneutralization assay [4].…”
Section: Introductionmentioning
confidence: 99%
“…MGEs cover different types of event and contexts such as public and private celebrations, festivals, religious events and pilgrimages, sporting and touristic events, and political meetings. The crucial role of MGEs in the global propagation of the disease has been evidenced in several countries, including China [ 3 ], Iran [ 4 ], Malaysia [ 5 ], Italy [ 6 ], Spain [ 7 ], France [ 8 ], Germany [ 9 ], Jordan [ 10 ], Malta [ 11 ], Switzerland [ 12 ], and Malawi [ 13 ]. Significant international efforts have been made to implement specific measures, risk assessment and surveillance, and event cancellations in order to prevent the spread of SARS-CoV-2 from MGEs [ 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Religious and other large gatherings have played a significant role in SARS-CoV-2 spread since 2020 [ 15 - 18 ]. Imported cases serve as sentinel events for affected countries which are unable to monitor emerging variants.…”
Section: Discussionmentioning
confidence: 99%